THE INFLUENCE OF “METAI” BY KRISTIJONAS DONELAITIS ON SIMONAS DAUKANTAS’ TEXTS - BONČKUTĖ, ROMA (Knygotyra, 2015)
The article analyses Simonas Daukantas’ autograph “Donelejtisa poratuj kolejno“ which consists of 200 words from Kristijonas Donetaitis’ poem “Metai” (The Seasons) and has never been studied by linguists. The author of the article brings forward and tries to prove the hypothesis that Metai is the main Lithuanian prototext of Daukantas. The purpose of the article is to discuss the influence of Donelaitis’s Metai on the language of Daukantas early historical texts. It introduces the manuscript of Daukantas “Donelejtisa poratuj kolejno“, never studied before, inquires its history and determines the nature of influence exerted by Donelaitis’ Metai on the language of Daukantas’ historical texts. Since the heritage of Daukantas’s publications is relatively large, the article commences with the earliest of his works: Darbay senuju Lituwiu yr Zemaycziu (about 1822–1825), Istoryje Ƶemaytyszka (prieš 1834), BUDĄ Senowęs–Letuwiu Kalnienu ir Ƶamajtiu (1845). In their analysis, the text lignuistics and some principles of intertextual theory are applied. In the article, the following questions are discussed: why could Daukantas be considered as an exemplary reader of Donelaitis’s Metai, what writings formed his attitude towards the history, religion and culture of Prussia. Daukantas knew the writings of the 17–19th century Prussia’s historians and the theoreticians of early German Romantism. It is supposed that the study of Prussia’s history and 18th century German authors’ ideas concerning the value of the native language and significance of the national spirit greatly influenced Daukantas’s worldview. He believed that the Lithuanian language had an equal right to exist along with the languages of big nations. His attitude towards the Lithuanian language coincides with that of Donelaitis. Both authors based their creativity on the examples of the Lithuanian language and were in opposition to the policy of Russification and Germanisation correspondingly. Daukantas and Donelatis were similar to each other in many aspects. In the beginning, the article analyses and comes to conclusion that it was written before 1838; then it investigates the influence of Metai on Daukantas’ historical texts. In the Darbai (Works) and Istorija Žemaitiška (Samogitian History), both written before 1838, there are many words found in the autograph. This fact allows us to conclude that the above mentioned collection of words was intended not so much for the composition of some text but rather for a new dictionary. Moreover, the study shows that Daukantas not only borrowed amply from Donelaitis’ lexicon but also developed it making neologisms. He frequently used secondary predication constructions characteristic of Donelaitis. The rhythmical structure of his sentences and word intonation was influenced by Donelaitis’ hexameter. Metai determined the nature of artistic and rhetoric means used by Daukantas in his historic works.